2017
DOI: 10.1021/acschemneuro.7b00285
|View full text |Cite
|
Sign up to set email alerts
|

Microchip Circulation Drastically Accelerates Amyloid Aggregation of 1–42 β-amyloid Peptide from Felis catus

Abstract: The amyloid aggregation process of amyloid β peptide is responsible for Alzheimer's disease, affecting millions of elderly people worldwide. Although there has been a great deal of attention directed toward tackling this disease, still no medicine has been found for this fatal disorder. To address this challenge, it is vital to thoroughly understand the molecular mechanism underlying the amyloid peptide aggregation process, as well as seek substances that could hamper this aggregation. In order to shed light o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
(96 reference statements)
0
6
0
Order By: Relevance
“…It was shown that the addition of a depolymerization event (leading to the formation of a monomer and a (i–1) fibril)) to primary and secondary nucleation and elongation steps suffices to reproduce the time evolution of fibril concentrations at different shear rates . Similar kinetics behavior was reported for Aβ42 under fluid flows …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the addition of a depolymerization event (leading to the formation of a monomer and a (i–1) fibril)) to primary and secondary nucleation and elongation steps suffices to reproduce the time evolution of fibril concentrations at different shear rates . Similar kinetics behavior was reported for Aβ42 under fluid flows …”
Section: Resultsmentioning
confidence: 99%
“…112 Similar kinetics behaviour was reported for Aβ42 under fluid flows. 113 While shear-induced monomeric protein dynamics were explored by experimental 114,115 and computational [116][117][118][119][120] studies, and lipid systems were also investigated under shear flows, [121][122][123][124] we still lack an atomic description of Aβ aggregates under fluid flows in the bulk solution and at the surface of membranes. Yet is it known that flowing acting on the membrane surface showed desorption, diffusion and collision of Aβ-lipid aggregates forming larger plaque-like aggregates.…”
Section: Protein Self-assembly Near In Vivo Conditionsmentioning
confidence: 99%
“…Because the secondary structure of Aβ determines its cytotoxicity, changes in CSF flow due to aging or disorders , may increase toxicity by altering Aβ conformation. Furthermore, flow increases intermolecular alignment and decreases the energy barrier for nucleation, the molecular effects of which have been confirmed via the flow-dependent modulation of nucleation, fibril growth, and other intra- and intermolecular processes of Aβ and other biological macromolecules. However, these studies examined Aβ in the absence of a cell membrane ( i.e. , stirring or shaking bath; Figure ) and did not evaluate the role of flowing condition on Aβ–lipid interactions and flow-triggered cytotoxicity.…”
mentioning
confidence: 99%
“…Mild shearing of Aβ-containing solutions has been shown to be sufficient to initiate fibril formation despite the very low total amount of energy and rate of energy input, which is reported to be less than that needed for the breakage of one hydrogen bond per molecule [ 22 ]. There is a recent report that micro-fluid flow of Aβ, modeling blood flow through very narrow flow paths, induced Aβ aggregation [ 32 ]. A critical paper reports that very gentle shear induces spectral changes that indicate subtle conformational changes in many different types of proteins [ 25 ], including Aβ (L. Ashton, private communication).…”
Section: In Vivo Shearmentioning
confidence: 99%